Balance, gait and quality of life in Parkinson's disease: Effects of whole body vibration treatment - Ludmylla Teixeira Soares; Aldo José Fontes Pereira; Lílian Danielle Paiva Magno; Hugo de Melo Figueiras; Luciane Lobato Sobral
Introduction Parkinson's disease (PD) is a neurodegenerative disorder, which triggers limitations and disability in people. Therefore, rehabilitation therapy is widely recommended in patients with PD, especially those who do not respond to pharmacological treatment.Objective Evaluate the effect of a protocol of Whole-body Vibration (WBV) in balance, gait and Quality of Life (QOL) of patients with PD, who do not respond to pharmacological treatment.Methods It was performed 12 sessions of a protocol WBV (squat, plantar flexion, isometric contraction of members and single-leg balance), with three sets each, at a vibrating platform (2mm and 35Hz) in 10 PD patients. By the first 3 sessions, patients underwent 20 seconds of exercise and 20 seconds of rest. After the third session, the treatment was 40 seconds of exercise and 20 seconds of rest. The Tinetti Test was applied before and after treatment to assess balance and gait, and the Parkinson's Disease Quality of Life-questionnaire (PDQL-BR), to evaluate the PDQL-BR and its subcategories: Parkinson, Systemic, Social and Emotional.Results Treatment did not significantly change the balance (p = 0.438), QOL issue in Emotional (p = 0.450) and Social (p = 0.171), but improved gait (p = 0.003), the Tinetti (p ≤ 0.001), the quality of life in items Parkinson (p ≤ 0.001), Systemic (p ≤ 0.001) and PDQL-BR (p ≤ 0.001).Conclusions WBV exercises on the vibrating platform, according to the parameters used, showed promising results that encourage its use to improve the clinical conditions related to disorders of gait, balance and QOL in patients with PD.